2012
DOI: 10.1111/j.1476-5381.2012.01983.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 receptors mediate the effects of corticotropin‐releasing factor on the reinstatement of cocaine seeking and expression of cocaine‐induced behavioural sensitization

Abstract: BACKGROUND AND PURPOSEThe endocannabinoid and corticotropin-releasing factor (CRF) systems have been implicated in several long-lasting behavioural effects of prior cocaine experience. The present experiments were designed to probe functional interactions between endocannabinoids and CRF by testing the role of cannabinoid CB1 receptors in cocaine-related behaviours induced or mediated by CRF. EXPERIMENTAL APPROACHIn Experiment 1, rats trained to self-administer cocaine were pretreated with the CB1 receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Without further evidence to help resolve this discrepancy, one interpretation could be that eCB signaling contributes to stress-induced alcohol consumption but not stress-induced relapse following cessation. Similar discrepancies have been found with cocaine whereby CB1 receptor antagonism does not block footshock-induced reinstatement of cocaine-seeking behavior (De Vries et al, 2001;Kupferschmidt et al, 2012) but has been found to reverse the reinstatement of cocaine-seeking behavior in response to swim stress (Vaughn et al, 2012) or direct administration of CRH (Kupferschmidt et al, 2012). Here it is possible that the stress modality itself could have differential effects on eCB signaling (as discussed above) in which eCB signaling could be important for some forms of stress-induced cocaine reinstatement, while it is dispensable for others.…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effesupporting
confidence: 64%
“…Without further evidence to help resolve this discrepancy, one interpretation could be that eCB signaling contributes to stress-induced alcohol consumption but not stress-induced relapse following cessation. Similar discrepancies have been found with cocaine whereby CB1 receptor antagonism does not block footshock-induced reinstatement of cocaine-seeking behavior (De Vries et al, 2001;Kupferschmidt et al, 2012) but has been found to reverse the reinstatement of cocaine-seeking behavior in response to swim stress (Vaughn et al, 2012) or direct administration of CRH (Kupferschmidt et al, 2012). Here it is possible that the stress modality itself could have differential effects on eCB signaling (as discussed above) in which eCB signaling could be important for some forms of stress-induced cocaine reinstatement, while it is dispensable for others.…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effesupporting
confidence: 64%
“…In the present study we did not find a difference in plasma corticosterone levels between the five treatment groups. Average plasma levels were 119.0 ± 5.9 ng/mL, a value above what has been reported for non-stressed Long-Evans male rats in some (Konkle et al 2010) but not other (Kupferschmidt et al 2012) studies. For example, corticosterone levels in Long-Evans rats prior to a stress challenge but just following a behavioral test were approximately 350 ng/mL (Kupferschmidt et al).…”
Section: Discussionmentioning
confidence: 50%
“…The results agree with other evidence that activation of extrahypothalamic CRF sites subserves stress-induced reinstatement behavior (Shaham et al, 1997;Erb et al, 1998;Wang et al, 2005;Wang et al, 2006;Blacktop et al, 2011). Consistent with this hypothesis, intra-VTA (Wang et al, 2005) or intracerebroventricular (Blacktop et al, 2011;Kupferschmidt et al, 2011;Brown et al, 2012;Buffalari et al, 2012;Kupferschmidt et al, 2012) infusion of CRF can reinstate cocaine-seeking behavior in rats.…”
Section: Stress-induced Reinstatementmentioning
confidence: 73%